2014
DOI: 10.1007/s10555-014-9520-6
|View full text |Cite
|
Sign up to set email alerts
|

Function and regulation of MTA1 and MTA3 in malignancies of the female reproductive system

Abstract: The family of metastasis-associated (MTA) genes is a small group of transcriptional co-regulators which are involved in various physiological functions, ranging from lymphopoietic cell differentiation to the development and maintenance of epithelial cell adhesions. By recruiting histone-modifying enzymes to specific promoter sequences, MTA proteins can function both as transcriptional repressors and activators of a number of cancer-relevant proteins, including Snail, E-cadherin, signal transducer and activator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 96 publications
0
13
0
1
Order By: Relevance
“…MTA-1 was discovered in 1993, demonstrating high expression levels with high metastatic potential in rat breast cancer cells ( 26 ). Subsequently, it was confirmed that MTA-1 is involved in the invasion and metastasis of tumors, and is involved in regulating a variety of other malignant tumor processes, including cell proliferation, angiogenesis and resistance to chemotherapy ( 26 30 ). Furthermore, MTA-1 is associated with high recurrence and a poor prognosis, and eventually causes cancer.…”
Section: Discussionmentioning
confidence: 99%
“…MTA-1 was discovered in 1993, demonstrating high expression levels with high metastatic potential in rat breast cancer cells ( 26 ). Subsequently, it was confirmed that MTA-1 is involved in the invasion and metastasis of tumors, and is involved in regulating a variety of other malignant tumor processes, including cell proliferation, angiogenesis and resistance to chemotherapy ( 26 30 ). Furthermore, MTA-1 is associated with high recurrence and a poor prognosis, and eventually causes cancer.…”
Section: Discussionmentioning
confidence: 99%
“…MTA1 is involved in the positive regulation of protein autoubiquitination. In fact, this gene has been characterized as an important oncogene facilitating cervical cancer progression and metastasis [ 16 , 17 ]. Knockdown of MTA1 partly restores p53 and E-cadherin expression in cervical cancer cells and subsequently decreases their invasion, migration, and adhesion capabilities [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, information about the impact of MTA alterations on the survival rates of cancer patients is only available for a few cancer-types such as hepatocellular carcinomas wherein MTA1 overexpression has been shown to be associated with a poorer survival (reviewed by Toh and Nicholson, 2014). While MTA3 may be either downregulated in cancer such as in breast cancer and endometrioid adenocarcinomas (Brüning, A. et al, 2014) or upregulated in human cancer such as in non-small cell lung cancer (Li et al, 2013b), human placenta and chorionic carcinoma cells (Brüning, A. et al, 2009). The nature of relationship between the status of MTA3 and survival of cancer patients is somewhat not fully examined at the moment.…”
Section: Cellular Functions Of Mta Familymentioning
confidence: 99%